2017
DOI: 10.1016/j.apergo.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long term driving on driver discomfort and its relationship with seat fidgets and movements (SFMs)

Abstract: Discomfort in vehicle seats is a multifactorial problem with large increases in discomfort occurring during extended duration driving. Due to the nature of driver discomfort, previous research has found it difficult to accurately quantify long term driver discomfort via the use of objective measures. This paper reports a laboratory study that investigates a novel objective measure of long term driver discomfort and its correlation with subjective discomfort ratings. Analysis of driver's seat fidgets and moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 23 publications
8
48
2
1
Order By: Relevance
“…The more the head moved to another position, the higher the participant rated the discomfort of the pillow. This is in line with the findings of Sammonds, Fray, and Mansfield (), who suggested that, as car drivers’ subjective discomfort increases, the frequency of subjects’ seat fidgets and movements increases congruently. Also Cascioli, Liu, Heusch, and McCarthy (); Jackson, Emck, Hunston, and Jarvis (); Le, Rose, Knapik, and Marras (); and Na, Lim, Choi, and Chung () found that greater in‐chair movement is related to increased discomfort.…”
Section: Discussionsupporting
confidence: 92%
“…The more the head moved to another position, the higher the participant rated the discomfort of the pillow. This is in line with the findings of Sammonds, Fray, and Mansfield (), who suggested that, as car drivers’ subjective discomfort increases, the frequency of subjects’ seat fidgets and movements increases congruently. Also Cascioli, Liu, Heusch, and McCarthy (); Jackson, Emck, Hunston, and Jarvis (); Le, Rose, Knapik, and Marras (); and Na, Lim, Choi, and Chung () found that greater in‐chair movement is related to increased discomfort.…”
Section: Discussionsupporting
confidence: 92%
“…Body maps have been used in many studies to evaluate driver discomfort (Gyi and Porter, 1999, Porter et al, 2003, Hiemstra-van Mastrigt et al, 2015, Sammonds et al, 2017a. A body map showing six body areas (neck, shoulders, upper back, lower back, buttock area and ankles) with a six-point Discomfort Scale defined in ISO 2631-1 (International Organization For Standardization, 1997) was used.…”
Section: Data Collectionmentioning
confidence: 99%
“…Driver Seat Fidget Movements (SFMs) also known as Discomfort Avoidance Behaviours (DABs) or 'in chair movement' can be used as a measure of driver discomfort (Malik et al, 1991;Maradei et al, 2017, Sammonds et al, 2017a). For the current study SFMs are movements judged to be related to physical discomfort and not to the driving task.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature surveys show this concern regarding user comfort on the effects of WBV vibration on vehicle seats, such as in the works of Zhang, Qiu and Griffin (2015) and Ji, Eger and Dickey 2017and Nawayseh's work (2015), that investigates the effect of foam and air in seat cushions in the transmissibility of vibration in car and heavy vehicle passengers. The effect of discomfort on drivers, when exposed to long periods driving (Sammonds et al, 2017) and aircraft passenger discomfort assessment (Ciloglu et al, 2015) also indicate that there is a recent concern in the study of materials and solutions to mitigate passenger vibrations in such types of transportation. Unfortunately, from the literature review in the national literature, no studies were found related to the evaluation of the level of exposure to vibration in urban trains, which shows that this study is a pioneer in this type of evaluation.…”
Section: Effects Of Vibration In Human Bodymentioning
confidence: 99%